Permanência e mutação no discurso do automóvel em São Paulo: uma análise sociossemiótica - Boanova, Nathalia Guimarães (2017)
The following research aims to investigate how the city of São Paulo, through the plastic traces which constitute its spaces as well as its discursive choices act as a subject which modalizes its citizenships and establishes mechanisms which reinforce a model of mobility that prioritizes the car. Also on how the city places the automobile in the position of a subject which allows it to make-do a city where the traces of terminativity and impermanence are dominant. It also examines the regimes of interaction and meaning that the car establishes with this subject-city and with its other subjects in order to understand whether an axiomatic change is possible in this context or not. The corpus of this dissertation is composed by diachronic and synchronic elements, considering the enunciative choices from the past which have left their marks on the traces of the city, including the cultural and media manifestations concerning our object, as well as the practices of life observed in the metropolis, taken here as a counter-discourse, especially those which occur in Avenida Paulista on the days of Paulista Aberta and at the Minhocão during the hours in which it is closed for the passage of cars. In order to comprehend such a corpus, as well as the discursive matters and the aspectuality of the city, this work grounds itself in the discursive semiotics of A. J. Greimas and the continuity of his work given by the social semiotics of Eric Landowski, key to understanding the regimes of interaction and meaning, especially in regard to the actors of urban mobility. As to the practices of life in the city, we relied on the work developed by Ana Claudia de Oliveira, in the plastic semiotics of Jean-Marie Floch, as well as the concepts of Michel de Certeau and its his theory regarding the enunciations of the city and the rights to urban space. We were able to then establish that the enunciative choices made throughout the years by the destinators of the city have left deep marks which make the existence of counter-discourses capable of ressemantizing these traces difficult, especially considering the fact that they attempt to reconstitute the city as a space of permanence and enjoyment, when its rhythmic trace is still imposed by the speed of the cars and its structure. We understood how this object-subject of value is still the protagonist in this structure and in the ways of living in the city just like the way through which the counter-discourses have been appropriated by the same old private destinators in an attempt to reclaim this political-narrative space of visibility